Particle-size stratification of airborne antibiotic resistant genes, mobile genetic elements, and bacterial pathogens within layer and broiler farms in Beijing, China - Bai, Yuqiao; Sun, Xingbin; Guo, Yajie; Qiu, Tianlei; Xin, Huibo; Yu, Aoyuan; Wang, Xuming; Gao, Min (Environmental science and pollution research international, 2023)
The particle-size distribution of antimicrobial resistant (AMR) elements is crucial in evaluating their environmental behavior and health risks, and exposure to the fecal microbiome via particle mass (PM) is an important route of transmission of AMR from livestock to humans. However, few studies have explored the association between air and fecal AMR in farm environments from the perspective of particle-size stratification. We collected feces and PMs of different sizes from layer and broiler farms, quantified antibiotic resistance genes (ARGs), mobile genetic elements (MGEs), and human pathogenic bacteria (HPB) using Droplet digital PCR (ddPCR), and analyzed the bacterial communities based on 16S rRNA sequencing. The particle-size distributions of 16S rRNA and AMR elements were similar and generally increased with larger particle sizes in chicken farms. In broiler farms, we observed a bimodal distribution with two peaks at 5.8–9.0 μm and 3.3–4.7 μm. The dominant airborne bacterial phyla were Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidetes. The dominant phyla in the feces were the same as those in the air, but the order of relative abundance varied. The particle-size distributions of specific bacterial genera differed between the animal-farm types. Overall, the degree of association between feces and different particulates increased with increasing particle size. The microbial communities in the coarse particles were similar to those in fecal samples. Escherichia coli, Staphylococcus spp ., Campylobacter spp . , and sul 2 (sulfonamide ARGs) tended to attach to small particles. We highlight the particle size-specific relationship between fecal and air microbes involving ARGs, MGEs, and HPB and provide valuable information for comprehensively assessing the transmission of fecal microorganisms through the airpath and its environmental and occupational health risks.